Not Only What is Written Counts! Touchscreen Enhancing our Cognition and Language (Global Journal of Human-Social Science, 2020)
By bringing contributions from cognitive science and neuroscience, this article enhances the gestures approach including, manipulations on mobile devices as a new way of communicating and thinking. The paper reflects on the cognitive and linguistic implications that smartphones or tablets can bring to learning in general and mathematical education in particular. Both thinking and mathematics are dynamic. Through two examples from daily life, I advocate the need to understand the development of mathematical thinking as a conjunction of touchscreen, gesture, speech, dragging, writing, pictorial-register, etc. Taking into account the context of production, this bundle has a significant role in the linguistic-cognitive spectrum of humans.
Keywords: smartphone; tablets; language; cognition; mathematics education